Factors Influencing Household Food Security Among Irrigation Smallholders in North West Nigeria - Adeniyi, Daniel Adeoluwa; Dinbabo, Mulugeta F. (Journal of Reviews on Global Economics, 2019)
Motivation: Food insecurity remains a continuing global challenge in most parts of the developing world, including Nigeria. While considerable resources have been devoted to tackling the menace owing to its negative impacts on health and well-being, progress is rather slow and uneven across regions and countries. Indeed, much is yet to be explored on the conditions that result in food insecurity. The paper investigates household food security and the socio-economic factors that determine it among smallholders in the Middle Rima Valley Irrigation Project, Sokoto State, Nigeria. Novelty: The combination of both the Household Dietary Diversity Score (HDDS) and Food Consumption Score (FCS) to measure food security and the regression of these variables against socio-economic characteristics of smallholder households represent an innovative way of assessing the effect of socio-economic characteristics on food security status of smallholder households which has scarcely been done in literature. Methodology and Methods: Quantitative data were successfully collected from 306 randomly selected households using a well-structured questionnaire. The HDDS and FCS were used to assess household food security level, and multivariate regression was used to examine factors associated with food security. Data and Empirical Analysis: Results indicate that at least 45% of the households were food insecure. The relationship between HDDS and FCS was found to be moderate, but positive and statistically significant. This thus validates the food insecurity phenomenon in the study area. Food insecurity is influenced by household income, education, training, farming experience, livestock ownership, and farm size. The latter however emerged as the most significant factor influencing food security of smallholder households. Policy Considerations: Targeted interventions are recommended in the areas of social protection initiatives, human capacity development through farmer training, and market access. The latter is imperative as smallholders may lack the motivation to increase production in an era of inadequate access to market. Furthermore, there is also the need to improve infrastructure to enhance access to market, encourage sustainable intensification and provide access to credit facilities for increased cultivation.